2010
DOI: 10.1097/mnh.0b013e32833bfa4e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular physiology of the Rh ammonia transport proteins

Abstract: Purpose of review Recent studies have identified a new family of ammonia-specific transporters, Rh glycoproteins, which enable NH3-specific transport. The purpose of this review is to summarize recent evidence regarding the role of Rh glycoproteins in renal ammonia transport. Recent findings The Rh glycoproteins, RhAG/Rhag, RhBG/Rhbg and RhCG/Rhcg, transport ammonia in the form of molecular NH3, although there is some evidence suggesting the possibility of NH4+ transport. RhAG/Rhag is expressed only in eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…TAM excretion requires controlled interaction of basolateral uptake and apical release of TAM. In vertebrates, this process is potentially differentially mediated by Rhbg and Rhcg located in basolateral and apical membranes, respectively (Bishop et al, 2010;Weiner and Verlander, 2010), but in invertebrates such as crustaceans and bivalves, so far only one primitive Rh protein has been described (Martin et al, 2011;Zhang et al, 2012). Consequently, an alternative model of vesicular TAM trapping has been suggested for crustaceans involving VHA and the Rh protein located in the membranes of intracellular vesicles (Weihrauch et al, 2002).…”
Section: Mechanisms Of Tam Excretion In Bivalvesmentioning
confidence: 99%
See 1 more Smart Citation
“…TAM excretion requires controlled interaction of basolateral uptake and apical release of TAM. In vertebrates, this process is potentially differentially mediated by Rhbg and Rhcg located in basolateral and apical membranes, respectively (Bishop et al, 2010;Weiner and Verlander, 2010), but in invertebrates such as crustaceans and bivalves, so far only one primitive Rh protein has been described (Martin et al, 2011;Zhang et al, 2012). Consequently, an alternative model of vesicular TAM trapping has been suggested for crustaceans involving VHA and the Rh protein located in the membranes of intracellular vesicles (Weihrauch et al, 2002).…”
Section: Mechanisms Of Tam Excretion In Bivalvesmentioning
confidence: 99%
“…Recent studies have revealed that both passive diffusion of gaseous NH 3 and active NH 4 + transport are facilitated by specialized ion-transporting proteins (Weihrauch et al, 2009;Wright and Wood, 2009;Weiner and Verlander, 2010 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium also serves as principal nitrogen source for numerous microorganisms and plants, whereas it is mainly regarded as a blood pH regulator and a cytotoxic compound in mammals [8][9][10] . Three Mep-Amt proteins enable ammonium transport in Saccharomyces cerevisiae 11 .…”
mentioning
confidence: 99%
“…Prominent among these ammonia-transporting proteins are the Rh glycoproteins. Three mammalian Rh glycoproteins have been identified, Rh A glycoprotein, which is expressed specifically in erythroid cells, and the nonerythroid Rh glycoproteins, Rh B glycoprotein (Rhbg) and Rh C glycoprotein (Rhcg), which are expressed widely in ammonia-transporting tissues, including the kidney (29,30,32,33).In the kidney, Rhcg is expressed in the renal distal nephron and collecting duct, from the distal convoluted tubule (DCT) through the inner medullary collecting duct (8,10,20,28), where 60 -80% of final urinary ammonia is secreted. Evidence supporting a critical role for Rhcg in renal ammonia transport includes findings that 1) Rhcg transports NH 3 (reviewed in Ref.…”
mentioning
confidence: 99%
“…1 Increasingly, the "traditional" theory of passive NH 3 diffusion and NH 4 ϩ trapping is being replaced by one in which specific membrane proteins transport NH 3 or NH 4 ϩ , enabling facilitated and regulated membrane NH 3 and NH 4 ϩ transport (32,33). Prominent among these ammonia-transporting proteins are the Rh glycoproteins.…”
mentioning
confidence: 99%